Evolution of environmental sex determination via juvenile hormone–induced gene co-option in Daphnia - Yugo Takahata; Moe Kusajima; Shione Abe; Misato Okamoto Miyakawa; Tomohiro Suzuki; Hideo Dohra; Hitoshi Miyakawa (Proceedings of the National Academy of Sciences, 2026)
Juvenile hormone (JH) exerts pleiotropic effects in insects, regulating not only metamorphosis and reproduction but also caste differentiation, morphogenesis, and diapause. How such diverse functions evolved from the ancestral role of JH remains poorly understood. The water flea, Daphnia , provides a striking case in which JH governs environmental sex determination (ESD) by inducing male production. Nonetheless, the molecular pathway linking maternal JH signaling to sex determination has remained unknown. Here, we identify the circadian gene, vrille ( Dpvri ), as a direct transcriptional target of JH signaling. Reporter assays revealed that Dpvri is activated by the JH receptor complex (Methoprene-tolerant/steroid receptor coactivator) via newly acquired 9-bp JH response elements (9 bp-JHREs) in its regulatory region, whereas the beetle ( Tribolium ) vri gene lacks such elements and did not show JH-responsive expression. This demonstrates that the presence or absence of specific regulatory sequences underlies interspecific differences in JH responsiveness. CRISPR/Cas9 mutagenesis of a single JHRE substantially reduced JH-dependent Dpvri expression and elevated the threshold for male induction, demonstrating its causal role in vivo. Comparative sequence analyses showed that JHREs in vri are conserved in the Cladocera, but absent in the crustacean, Artemia , suggesting that their emergence coincided with the origin of ESD in this lineage. These findings reveal the evolutionary co-option of vri into the JH pathway via acquisition of a JHRE, providing a mechanistic explanation for diversification of JH functions in arthropods.